FLEXIBILITY OF LANGUAGE EXPERIENCE IN INDONESIAN HUMOR CULTURE (SYSTEMIC FUNCTIONAL GRAMMAR) (Lingua, 2019)
The purposes of this research is to find flexibility of Indonesian humor culture using language experience. This research is a descriptive-qualitative research. Collecting data uses listening method by using basic technique of tap and then write. Analyzing data in this research uses equalizing reference method by using comparing technique to support codification, reduction, presentation, and interpretation such as work design of qualitative research. The results of this research, those are: exploiting the common truth that people already know; changing constituents with his language experience; putting false pronouns deliberately; conveying something incomplete; diverting different languages; providing an unrelated response at all; exploiting the language gap to distort its meaning; conveying something unnatural, absurd, even impressed controversy